(untitled) (TERRA LATINOAMERICANA, 2025)
In Mexico, chili (Capsicum chinense Jacq.) is a crop of economic and nutritional importance whose production is affected by soil phytopathogens, with biological control being a beneficial tool for the ecosystem; in the case of M. anisopliae, its limitation is sensitivity to environmental factors that reduce its effectiveness, so coverage using a polymer matrix is ​​feasible to provide protection, for this reason, the characterization of encapsulated spores of M. anisopliae and its effect on the growth of chili plants inoculated with Fusarium oxysporum was carried out. The encapsulation was done by ionic gelation with sodium alginate and calcium chloride, the water retention and absorption capacity of the encapsulates was analyzed, as well as the viability of the spores and their antagonistic activity in vitro by dual confrontation on F. oxysporum. The capacity of the encapsulation and the spore suspension of M. anisopliae for the control of Fusarium in C. chinense Jacq. plants was also compared. The encapsulate CEM2 (3000 μm ∅, 1 M CaCl2) with 43.4% humidity and 48.3% swelling, showed the highest spore survival of 96% and viability of more than 90% during 75 days of storage at 37 °C. CEM2 demonstrated its antagonistic capacity in vitro by inhibiting the radial growth and sporulation spores of F. oxysporum 62.9 and 60.5% respectively. The application of the encapsulate CEM2 and the suspension spores of M. anisopliae reduced the effect of Fusarium inoculation in chili plants since the values ​​of height, stem diameter and chlorophyll were higher than diseased plants and demonstrated that it promotes growth when applied to healthy plants.